The overview of software for computer simulations in profile physics learning - Arnold E. Kiv; Olexandr V. Merzlykin; Yevhenii O. Modlo; Pavlo P. Nechypurenko; Iryna Yu. Topolova (CTE Workshop Proceedings, 2019)
The paper deals with the possibilities of using specialized (virtual labs and simulators, software for natural process simulation) and general (programming languages and libraries, spreadsheets, CAS) software in school researches. Such software as virtual labs, software for natural process simulation, programming languages and libraries in school researches can be used to simulate phenomena that cannot be learned in a school lab (for example, for modeling a radioactive decay or for demonstrating the states of relativistic mechanics). Also, virtual labs in school practice are usually used in those cases where students cannot perform an experiment in real labs. For example, it is convenient for distance learning. The using of programming languages and libraries in physics learning research requires both students’ physics research competencies and programming competencies. That is why using this software in physics classes can hardly be recommended. However, programming languages and libraries can become a powerful tool for the formation and development of research competencies of physics students in extracurricular learning activities. The implementation of the spreadheets and the CAS in school physics researches is the easiest and has its benefits.